2019
DOI: 10.1002/chem.201805878
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Intramolecular Formal Insertion Reaction of Rh–Nitrenes into an Amide Bond Over C−H Insertion

Abstract: The past few decades have witnessed extensive efforts to discloset he unique reactivity of metal-nitrenes, because they could be ap owerful synthetic tool for introducing the amine functionality into unactivated chemical bonds. The reactivity of metal-nitrenes, however,i sc urrently mainly confined to aziridination (an insertion into aC =C bond) and CÀHa mination (an insertion into aC ÀHb ond). Nitrene insertion into an amide CÀNb ond, however,h as not been reported so far.I nt his work we have developedarhodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“… Dirhodium(II,II) complexes containing O , O ‘‐bridging ligands with structural motive OOC‐spacer‐COO: W1 , [250] W2 , [251] W3 , [252] W4 , [253] W5 , [254] W6 , [252] W7a R=H, [255] W7b R= t Bu, [256] W8 , [257] W9 , [188] W10 , [258] W11 , [258] W12 , [71] W13 [259] …”
Section: Overview Of Rh2a4 Paddlewheel Complexesmentioning
confidence: 99%
“… Dirhodium(II,II) complexes containing O , O ‘‐bridging ligands with structural motive OOC‐spacer‐COO: W1 , [250] W2 , [251] W3 , [252] W4 , [253] W5 , [254] W6 , [252] W7a R=H, [255] W7b R= t Bu, [256] W8 , [257] W9 , [188] W10 , [258] W11 , [258] W12 , [71] W13 [259] …”
Section: Overview Of Rh2a4 Paddlewheel Complexesmentioning
confidence: 99%
“…The process begins with an ylide formation by the coordination of a suitably located lactam to the metallonitrene, followed by the migration of the acyl group to the nitrogen. The authors identified that an electronically optimized Rh 2 (esp) 2 catalyst selectively formed 35 through the ylide formation ( Scheme 11 a ), [49] whereas a silver complex ligated by an achiral BOX ligand yielded C−H amination product 36 ( Scheme 11 b ) [50] …”
Section: Intramolecular Nitrene Transfersmentioning
confidence: 99%
“…In our continuing research toward discovering unknown reactivities of metal–nitrene species, we reported nitrene insertion reactions into an amide C–N bond using an electronically tuned Rh­(II) dimer complex . The amide insertion reaction proceeds through the generation of a Rh-associated N + – N – ylide with amide functionality, , followed by [1,2]-acyl transfer, which is thermodynamically disfavored yet kinetically preferred to the competing C–H insertion process.…”
Section: Introductionmentioning
confidence: 99%